Comparative Analyses of Poly(ADP-Ribose) Polymerase Inhibitors. (December 2022) - Guha, Mausumee; Sobol, Zhanna; Martin, Mathew; Hemkens, Michelle; Sung, Tae; Rubitski, Elizabeth; Spellman, Richard; Finkelstein, Martin; Khan, Nasir; Hu, Wenyue
Poly(ADP-ribose) polymerase inhibitors (PARPi) are approved as monotherapies in BRCA1/2 -mutated (m BRCA1/2 ) metastatic breast and ovarian cancers, and in advanced pancreatic and metastatic castration-resistant prostate cancers. Differential safety profiles across PARPi necessitate improved mechanistic understanding of inhibitor differences, especially with expansion of PARPi indications and drug combinations. Here, we report in vitro evaluations of PARPi (–/+ PARP trapper temozolomide, TMZ) with reference to total clinical mean concentration average or maximum (tCavg, tCmax ), to elucidate contributions of primary pharmacology and structural differences to clinical efficacy and safety. In biochemical assays, rucaparib and niraparib demonstrated off-target secondary pharmacology activities, and in selectivity assays, talazoparib, olaparib, and rucaparib inhibited a broader panel of PARP enzymes. In donor-derived human bone marrow mononuclear cells, only olaparib both increased early apoptosis and decreased the cell viability half inhibitory concentration (IC50 ) at ≤ tCavg, whereas other PARPi only did so in the presence of TMZ. In cancer cell lines with DNA damage repair mutations, all PARPi decreased cell viability in H1048 but not TK6 cells, and only talazoparib decreased cell growth in DU145 cells at ≤ tCavg concentrations. When combined with low dose TMZ, only talazoparib left-shifted the functional consequences of PARP trapping (S-phase arrest, apoptosis, S-phase double-stranded breaks) and reduced cell viability/growth in TK6 and DU145 cell lines at ≤ tCavg, whereas the other inhibitors required high-dose TMZ. Our study suggests structural differences across PARPi may contribute to differences in PARP selectivity and off-target activities, which along with distinct pharmacokinetic properties, may influence inhibitor-specific toxicities in patients.